1987
DOI: 10.1113/expphysiol.1987.sp003056
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Maturation of the Small Intestine in the Fetal Sheep. Ii. The Effects of Exogenous Cortisol

Abstract: SUMMARYThe effect of cortisol on small intestinal maturation was investigated in catheterized fetal sheep by infusing 2 mg cortisol/d between 105 and 115 d gestation (term ca. 147 d). This treatment resulted in a fivefold increase in plasma cortisol compared with catheterized control fetuses of the same age. There were no detectable changes in enterocyte morphology after the cortisol infusion; the size and density of most intestinal components were largely unaffected by the treatment. By contrast, the kinetics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
22
1

Year Published

1989
1989
2005
2005

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 23 publications
1
22
1
Order By: Relevance
“…In contrast, we have previously reported a significant increase in ileal epithelial and goblet cell numbers when newborn mice are treated with early postnatal dexamethasone (DEX) (Gordon et al 2001a), suggesting a proliferative mechanism of hypertrophy that is potentially ever present in the neonate. Similar findings have been reported in fetal sheep when exposed to antenatal steroids, indicating that the capacity extends backwards into gestation (Trahair et al 1987). These paradigms have clinical relevance to an emerging and highly morbid neonatal disease known as spontaneous intestinal perforation (also called focal small bowel perforation) which afflicts 5-10% of all extremely low birth weight infants (Garland et al 1999, Gordon et al 1999, Stark et al 2001.…”
Section: Introductionmentioning
confidence: 64%
“…In contrast, we have previously reported a significant increase in ileal epithelial and goblet cell numbers when newborn mice are treated with early postnatal dexamethasone (DEX) (Gordon et al 2001a), suggesting a proliferative mechanism of hypertrophy that is potentially ever present in the neonate. Similar findings have been reported in fetal sheep when exposed to antenatal steroids, indicating that the capacity extends backwards into gestation (Trahair et al 1987). These paradigms have clinical relevance to an emerging and highly morbid neonatal disease known as spontaneous intestinal perforation (also called focal small bowel perforation) which afflicts 5-10% of all extremely low birth weight infants (Garland et al 1999, Gordon et al 1999, Stark et al 2001.…”
Section: Introductionmentioning
confidence: 64%
“…In rodents, it is possible that the glucocorticoid-induced changes in enzyme activity mainly result from increases in enterocyte turnover and replacement of the villus cell population (6,8,35). An increased enterocyte turnover has also been reported in the fetal sheep after cortisol administration (36). However, increased cell proliferation rate in young animals does not always lead to a simultaneous increase in sucrase activity and loss of lactase activity (37,38), and hence other factors must be involved.…”
Section: Discussionmentioning
confidence: 92%
“…We have furthermore demonstrated that growth of intestinal structures is reduced after fetal bilateral adrenalectomy (Trahair et al, , 1987a. Adrenalectomy also caused a reduction in enterocyte migration, while early cortisol infusion resulted in increases in both the PCL and migration rates (Trahair et al, 1987b). In the sheep fetus the adrenal produces cortisol in response to hypophyseal ACTH from about 120 days onwards (Wintour, 1984).…”
Section: Introductionmentioning
confidence: 95%